Tetraspanins as Organizers of Antigen-Presenting Cell Function - Saiz, Maria Laura; Rocha-Perugini, Vera; Sánchez-Madrid, Francisco (Frontiers in Immunology, 2018)
Professional antigen-presenting cells (APCs) include dendritic cells, monocytes and B cells. APCs internalize and process antigens, producing immunogenic peptides that enable antigen presentation to T lymphocytes, which provide the signals that trigger T-cell activation, proliferation and differentiation, and lead to adaptive immune responses. After detection of microbial antigens through pattern recognition receptors (PRRs), APCs migrate to secondary lymphoid organs where antigen presentation to T lymphocytes takes place. Tetraspanins are membrane proteins that organize specialized membrane platforms, called tetraspanin-enriched microdomains (TEMs), which integrate membrane receptors, like PRR and major histocompatibility complex class II (MHC-II), adhesion proteins and signalling molecules. Importantly, through the modulation of the function of their associated membrane partners, tetraspanins regulate different steps of the immune response. Several tetraspanins can positively or negatively regulate the activation threshold of immune receptors. They also play a role during migration of APCs by controlling the surface levels and spatial arrangement of adhesion molecules and their subsequent intracellular signalling. Finally, tetraspanins participate in antigen processing, and are important for priming of naïve T cells through the control of T-cell co-stimulation and MHC-II-dependent antigen presentation. In this review, we discuss the role of tetraspanins in APC biology and their involvement in effective immune responses.